Poly(l-lactic acid) nucleation by alkylated carbon black. (21st September 2022) - D′Urso, Luciana; Acocella, Maria Rosaria; De Santis, Felice; Guerra, Gaetano; Pantani, Roberto
Abstract: Biodegradable polymers are raising an increasing interest as alternative to oil-based materials. Among available biodegradable polymers, the most promising is possibly poly(l -lactic acid) (PLLA), which can be produced from renewable resources at reasonable costs. However, PLLA has some processing limitations, mainly associated with slow melt crystallization kinetics. In this work, an attempt is made to overcome these PLLA limitations, by using different kinds of carbon-based nanofillers. PLLA compounds were prepared in a twin screw extruder and characterized mainly by gel permeation chromatography, rotational rheometry and differential scanning calorimetry. Alkylated carbon black (aCB) in PLLA compounds not only induces high melt thermal stabilization (as also occurs with other carbon based nanofillers) but also acts as a nucleating agent, thus reducing crystallization times. aCB nucleation of PLLA is possibly due to the well known tendency of hydrocarbon tails to form ordered local aggregates, when bounded to solid structural layers. Graphical abstract: Image 1 Highlights: Alkylated carbon black (aCB) in PLLA compounds not only induces thermal stabilization but also acts as a nucleating agent. PLLA compounds with 1.0 wt% of aCB present crystallization times reduced of at least ten times. Nucleation for PLLA crystallization is associated with the presence of long alkyl chains being bounded to graphitic layers. Ordered aggregates of hydrocarbon tails are expected to be crystallization nuclei of the linear aliphatic polyester.